Annual Survey of Jails: Jail-Level Data, 2011 ([Verlag nicht ermittelbar], 2012)
The Annual Survey of Jails (ASJ) is the only data collection effort that provides an annual source of data on local jails and jail inmates. Data on the size of the jail population and selected inmate characteristics are obtained every five to six years from the Census of Jails. In each of the years between the full censuses, a sample survey of jails is conducted to estimate baseline characteristics of the nation's jails and inmates housed in these jails. The 2011 Annual Survey of Jails is the 24th such survey in a series begun in 1982. The ASJ supplies data on characteristics of jails such as admissions and releases, growth in the number of jail facilities, changes in their rated capacities and level of occupancy, growth in the population supervised in the community, changes in methods of community supervision, and crowding issues. The ASJ also provides information on changes in the demographics of the jail population, supervision status of persons held, and a count of non-citizens in custody. Starting in 2010, BJS enhanced the ASJ survey instruments to address topics on the number of convicted inmates that are unsentenced or sentenced and the number of unconvicted inmates awaiting trial/arraignment, or transfers/holds for other authorities. In order to reduce respondent burden, the ASJ no longer collects data on conviction status by sex. Also new to the survey, data are collected on jails' operational capacity and design capacity. Incorporating enhanced capacity measurements enables BJS to describe more accurately the variation and volatility of inmate bed space and crowding, especially as they relate to safety and security in jails. To address more directly issues related to overcrowding and safety and security in jails, BJS started collecting data on staff and assaults against staff from the largest jails. In the modifications to the ASJ, starting in 2010, 335 jail jurisdictions (370 respondents) included with certainty in the ASJ sample survey were asked to provide additional information (forms CJ-5D or CJ-5DA) on the flow of inmates going through jails and the distribution of time served, staff characteristics and assaults on staff resulting in death, and inmate misconduct. The data presented in this study were collected in the Annual Survey of Jails, 2011. These data are used to track growth in the number of jails and the capacities nationally, changes in the demographics of the jail population and supervision status of persons held, the prevalence of crowding issues, and a count of non-United States citizens within the jail population. The data are intended for a variety of users, including federal and state agencies, local officials in conjunction with jail administrators, researchers, planners, and the public. The reference date for the survey is June 30, 2011.